The effects of school-based management on Indian government schools - GUHA, Panchali (Institutional Knowledge at Singapore Management University, 2022)
India institutionalized school-based management in 2009 by requiring all government schools to constitute school management committees, primarily staffed by parents, that would make decisions on school-related issues. This article utilizes school-level panel data from the state of Uttar Pradesh and uses a matched difference-in-difference estimation methodology to examine the effect of this policy on the provision of basic school infrastructure and services in government schools. It finds evidence that the policy resulted in improving the provision of libraries and medical checkups for students.